IMPLEMENTASI PERATURAN DAERAH KABUPATEN BOJONEGORO NO 23 TAHUN 2011 TENTANG PERCEPATAN PERTUMBUHAN EKONOMI DAERAH DALAM PELAKSANAAN EKSPLORASI EKSPLOITASI DAN PENGOLAHAN MIGAS - Kasiyani, Wiji; Purnaweni, Hartuti; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2015)
Abundant potential of oil and gas in Bojonegoro Regency East Java is expected to provide benefits to the Bojonegoro society, especially for the local labor. Bojonegoro district government through Bojonegoro district regulation No.23 of 2011 about the acceleration of region economic growth in the implementation of exploration exploitation and processing oil and gas provide liability to oil and gas companies that run mining activities in Bojonegoro to use local labor. This research aims to describe the implementation of local regulation, especially regarding use of local labor based on five indicators, namely policy accuracy, implementer, target, environment, and process. This research uses descriptive qualitative research methods. Based on the research results, these regulations have been implemented since 2012, but the implementation still not maximum. The main resistor factor this local regulation still not maximum implemented is qualification of local labor in Bojonegoro, nowadays most of the labor in Bojonegoro is un-skilled, semi skill to professional skills is very limited number and unable meet the need of the oil and gass company. To improve local labor qualifications do training funded by CSR of oil and gas companies. Thus, recomendation that can be given is to be implementation of more intensive training for local labor, reformulated clear indicator of the success of implementation of local regulations, and punishment for companies that do not run properly the Regulation must be completely executed, as long as this punihment have not been implemented by the firm.